ABO and Rh Blood Group Distribution in İstanbul Province (Turkey) - Zeyneb İrem Yüksel Salduz; Güven Çetin; Cumali Karatoprak; Aclan Özder; Mesut Bilginç; İlhami Gültepe; Ömer Gül (İstanbul Medical Journal, 2015)

(untitled)
Objective: An understanding of the distribution of blood groups in a city is useful for individuals in need. In this study, we aimed to determine the distribution rates of ABO and Rh blood groups in İstanbul Province.Methods: This retrospective study was conducted by investigating the records of 6041 healthy blood donors who visited the Bezmialem Vakif University Faculty of Medicine, Blood Bank, between 1st January, 2011 and 31st December, 2013. ABO and Rh blood groups were examined by lam agglutination, micro plate agglutination, or gel centrifugation methods.Results: In this study, the frequency of the blood groups A, O, B, and AB were found to be 43.44%, 33.02%, 15%, and 8.54%, respectively. Rh (+) positivity was determined in 5192 cases (85.95%) and Rh (-) negativity was determined in 849 cases (14.05%). The frequency of intra-group Rh was found to be 87.84% of Rh (+) and 12.16% of Rh (-) in blood group A, 87.52% of Rh (+) and 14.48% of Rh (-) in blood group O, 82.12% of Rh (+) and 17.88% of Rh (-) in blood group B, and 76.94% of Rh (+) and 23.06% of Rh (-) in blood group AB. A majority of the blood donors were males (92.42%), and 69.28% were in the age group of 25–44 years.Conclusion: ABO and Rh blood group distribution rates in our region were similar to the general rates in Turkey. There was a positive correlation between the frequency of ABO blood group type and Rh positivity rate in each group. We believe that the present study will contribute to the literature with respect to the database of blood groups.